2009
DOI: 10.1002/bsl.886
|View full text |Cite
|
Sign up to set email alerts
|

The effects of harassment severity and organizational behavior on damage awards in a hostile work environment sexual harassment case

Abstract: Community members reporting for jury duty (N = 128) read a sexual harassment trial summary in which harassment severity and the organization's sexual harassment policy and response were manipulated. Jurors who read the severe harassment scenario were more likely to agree that the plaintiff had suffered and should be compensated for her suffering and that the organization should be punished than were jurors who read the mild harassment scenario. When the organization had and enforced a sexual harassment policy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Many authors (Feather, 1996;Rind, Jaeger, & Strohmetz, 1995) have found that an increase in the severity of a crime corresponds to an increase in the judgment of responsibility toward the perpetrator and an increase in emotions in favor of the victim (Zummuner & Fischer, 1995), and more of these emotions are associated with a strong motivation to help him or her (Dijker & Raeijmaekers, 1999). Additionally, a study by Cass, Levett, and Kovera (2010) shows that jurors who read a severe harassment vignette in opposition to jurors who read a mild harassment vignette were more likely to agree that the plaintiff had suffered and should be compensated for his or her suffering and that the organization should be punished. Thus, when the kind of bullying act is WORKPLACE BULLYING AND VICTIMS' BEHAVIORS considered more serious (impacting somebody's health or being aggressive compared to isolating), we can think that a perpetrator will be judged more responsible and the victim will receive more help.…”
Section: Kinds Of Acts Judgments Of Responsibility and Help Givingmentioning
confidence: 94%
“…Many authors (Feather, 1996;Rind, Jaeger, & Strohmetz, 1995) have found that an increase in the severity of a crime corresponds to an increase in the judgment of responsibility toward the perpetrator and an increase in emotions in favor of the victim (Zummuner & Fischer, 1995), and more of these emotions are associated with a strong motivation to help him or her (Dijker & Raeijmaekers, 1999). Additionally, a study by Cass, Levett, and Kovera (2010) shows that jurors who read a severe harassment vignette in opposition to jurors who read a mild harassment vignette were more likely to agree that the plaintiff had suffered and should be compensated for his or her suffering and that the organization should be punished. Thus, when the kind of bullying act is WORKPLACE BULLYING AND VICTIMS' BEHAVIORS considered more serious (impacting somebody's health or being aggressive compared to isolating), we can think that a perpetrator will be judged more responsible and the victim will receive more help.…”
Section: Kinds Of Acts Judgments Of Responsibility and Help Givingmentioning
confidence: 94%
“…Sexual harassment involves a specific type of conduct (hostile environment or quid pro quo), both of which J. P. Vallano et al 836 primarily result in psychological injury (Cass et al, 2010). Compared with physical injuries, psychological injuries do not easily lend themselves to objective evidence (i.e., an X-ray) that is clearly visible to the jury.…”
Section: Outcome Severitymentioning
confidence: 98%
“…This issue is particularly germane to sexual harassment cases, which primarily involve psychological injury evidence (Cass et al, 2010). Despite legal requirements that focus liability judgments on the defendant's conduct (A.C. Smith & Greene, 2005) and sexual harassment law which de-emphasizes the role of psychological injury severity when making liability decisions (Harris v. Forklift Systems, 1993), this research illustrates that psychological injury severity affects liability judgments.…”
Section: Injury Severitymentioning
confidence: 98%
See 1 more Smart Citation
“…For many authors (Feather, 1996;Howe & Loftus, 1992;Rind, Jaeger, & Strohmetz, 1995), an increase in the severity of crime corresponds to an increase in the judgments of responsibility toward the perpetrator, the emotions in favor of the victim (Zummuner & Fischer, 1995), and more these emotions are associated with a strong motivation to help him or her (Dijker & Raeijmaekers, 1999). Additionally, a study of Cass, Levett, and Kovera (2010) has shown that jurors who read the severe harassment vignettes in opposition to jurors who read a mild harassment vignette were more likely to agree that the plaintiff had suffered and should be compensated for her suffering, and that the organization should be punished. Thus, when the kind of bullying act is considered as more serious (to impact on somebody's health or to aggress by opposition to isolate), we can think that a perpetrator will be judged more responsible and the victim will receive more help.…”
Section: Kinds Of Acts Judgments Of Responsibility and Help-givingmentioning
confidence: 99%